ANALYSIS OF THE DETERMINANTS OF GROWTH OF THE MIDDLE CLASS IN INDONESIA SHARIA ECONOMIC REVIEW - Khayriza Sinambela; Nurul Jannah; Muhammad Ikhsan Harahap (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
This study aims to examine the key determinants driving the growth of the middle class in Indonesia through the lens of Islamic economics, with particular emphasis on education, Islamic capital market investment, and Islamic bank financing. Employing a quantitative approach, the research utilizes multiple linear regression analysis on time series data spanning from 2021 to 2024, processed using SPSS 25. The findings reveal that all three variables exert a statistically significant and positive impact on middle-class expansion. Education contributes to human capital development and employability; Islamic capital market investment fosters asset accumulation and equitable wealth distribution; and Islamic bank financing enhances access to productive capital, particularly for small-scale entrepreneurs and transitioning lower-income households. Collectively, these factors account for 87.4% of the variance in middle-class growth, underscoring their pivotal role in shaping the Islamic economic ecosystem. The results underscore the imperative to elevate financial literacy, broaden inclusive education, and improve the accessibility of Sharia-compliant financial instruments to accelerate and sustain middle-class advancement. Future research is encouraged to incorporate sociocultural and regional variables—such as urban-rural dynamics, religious practices, and digital financial behavior—to capture more nuanced influences and further validate the resilience of the Islamic economic model in fostering inclusive development